1980
DOI: 10.1007/bf00433805
|View full text |Cite
|
Sign up to set email alerts
|

Long-term chlorpromazine in rhesus monkeys: Production of dyskinesias and changes in social behavior

Abstract: The daily administration of chlorpromazine (CPZ) in doses of 8--40 mg/kg over 113 weeks to four rhesus monkeys produced dyskinesias and alterations in social behavior. General activity and social interactions were reduced by CPZ treatment but social aggression was elevated during initial drug administration. These behaviors returned to normal when treatment was discontinued. Dyskinesias appeared during CPZ treatment, and two striking ones, gravel mouth and hand gesture, persisted for 12 weeks after drug withdr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Although not well established on the basis of existing data, there is a potentially more fundamental relationship between neuroleptic drug action and negative symptoms. Psychological and behavioral changes similar to negative symptoms (e.g., apathy, lack of spontaneity, and impaired affective arousal) have been induced in infrahuman primates (McKinney et al 1980; Carlson 1981; McKinney and Moran 1981) and nonpsychotic humans (Baldessarini 1980) by neuroleptic drugs. Furthermore, preclinical evidence suggests that the negative symptom-like effects of neuroleptic drugs cannot be simply ascribed to a generalized motor depression resulting from sedation.…”
Section: Treatment Of Secondary Negative Symptomsmentioning
confidence: 99%
“…Although not well established on the basis of existing data, there is a potentially more fundamental relationship between neuroleptic drug action and negative symptoms. Psychological and behavioral changes similar to negative symptoms (e.g., apathy, lack of spontaneity, and impaired affective arousal) have been induced in infrahuman primates (McKinney et al 1980; Carlson 1981; McKinney and Moran 1981) and nonpsychotic humans (Baldessarini 1980) by neuroleptic drugs. Furthermore, preclinical evidence suggests that the negative symptom-like effects of neuroleptic drugs cannot be simply ascribed to a generalized motor depression resulting from sedation.…”
Section: Treatment Of Secondary Negative Symptomsmentioning
confidence: 99%
“…Among other species of primates treated with haloperidol, TD has appeared in two of 21 rhesus (Bedard et al 1977;Paulson 1972Paulson , 1973, but not among 31 squirrel, eight green, or two iris monkeys (Casey et al 1980;Gunne and B~ir~iny 1976;Liebman and Neale 1980;Weiss and Santelli 1978). Chlorpromazine has been administered chronically to a total of 35 rhesus monkeys (Deneau and Crane 1969;Paulson 1972Paulson , 1973McKinney et al 1980), but only four (11%) displayed TD (McKinney et al 1980). The contention that TD was produced in the chlorpromazine-treated rhesus monkeys of Paulson (1972Paulson ( , 1973 is not tenable, because in those particular animals dyskinesias worsened after each injection and were not exacerbated by drug withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, because it is not convenient to administer neuroleptics to monkeys in the same way as given to humans (several times daily for many months), this is rarely the practiced drug regimen. Domino and Kovacic (1983), in fact, concluded that of 121 monkeys that have been given neuroleptics in several published studies, most developed only the acute dystonic or parkinsonism syndrome, and only 10 developed TD (some of those of Gunne and Barany, 1976;Bedard et al, 1977;McKinney et al, 1980). Kovacic and Domino (1984), Johansson (1989), and Gunne et al (1984) subsequently increased this sample, but the number of documented cases is clearly very low.…”
Section: Primate Studiesmentioning
confidence: 99%